1977
DOI: 10.1073/pnas.74.2.610
|View full text |Cite
|
Sign up to set email alerts
|

A rapid procedure for selective enrichment of photosynthetic electron transport mutants.

Abstract: Metronidazole (2-methyl-5-nitroimidazole-1-ethanol) is shown to be effective for the selective enrichment of mutants of Chlamydomonas reinhardtii that possess impaired photosynthetic electron transport. More than 99.91% of -type cells are killed when incubated in the presence of 6-10 mM metronidazole for 24 hr under illumination of 7500 lux. Survival of wild-type cells in darkness and of mutants that are blocked at different steps in photosynthetic electron transport is nearly 100% when incubated in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…Interestingly, pretreatment with RB increased methyl viologen sensitivity but had no impact on sensitivity to metronidazole. This could be related to differences in chemical structure or sites of action between these two compounds (70). The experiment was also reversed, this time pretreating with neutral red, hydrogen peroxide, methyl viologen, metronidazole, and tert-butyl hydroperoxide, and challenging with RB.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, pretreatment with RB increased methyl viologen sensitivity but had no impact on sensitivity to metronidazole. This could be related to differences in chemical structure or sites of action between these two compounds (70). The experiment was also reversed, this time pretreating with neutral red, hydrogen peroxide, methyl viologen, metronidazole, and tert-butyl hydroperoxide, and challenging with RB.…”
Section: Resultsmentioning
confidence: 99%
“…1A). We tested hydrogen peroxide, tert-butyl hydroperoxide (an organic peroxide capable of triggering lipid peroxidation chain reactions), metronidazole (a compound which generates superoxide only in the chloroplast) (70), and RB (a xanthene dye that produces 1 O 2 ‫ء‬ upon excitation by light) for the ability to induce an acclimation response. The response to RB was the most dramatic, with a significant proportion of pretreated cells surviving concentrations that killed all unpretreated cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High fluorescent colonies of C. reinhardtii were obtained following UV treatment and enrichment for photosynthetic electron transport mutants with metronidazole (Schmidt et al, 1977). To identify strains with defects in photosystem II biogenesis, the isolates were characterized by pulse labeling cells with 35SO$-in the presence of cycloheximide.…”
Section: R E Su Lts Lsolation Of Mutant 6225mentioning
confidence: 99%
“…This drug is specifically reduced by low-potential electron donors, such as ferredoxins and flavodoxins, and the reduced derivatives are toxic to cells (44). Previous reports have shown that metronidazole enrichment for electron transport mutants can be successful (21,46).…”
mentioning
confidence: 99%